Anti-diabetic Potential of some Spices Commonly used in Diet with other Pharmacological Activities: A Review - Chowdhury, Anita R.; Kundu, Sukalyan Kumar (Current Traditional Medicine, 2022)
Background: Diabetes mellitus is a chronic metabolic disorder, the prevalence of which is increasing alarmingly throughout the world and imposes a serious impact on the health of the population as well as national economies. Effective management and primary prevention are essential to decrease the burden of diabetes faced by all nations. Although different therapies are available for diabetes, no known therapy can completely cure the disease, and many of them have a number of side effects with other limitations like long-term treatment, expensiveness, and less availability. Hence, the present review has given an emphasis on common dietary materials to find out a readily available source of anti-diabetic agents. Objective: The purpose of this work is to explore the anti-diabetic properties of certain spices which are most frequently used in Bangladesh and reported for their use in traditional treatment of diabetes and/or investigated scientifically for anti-diabetic activity. Methods: Two electronic databases, namely Pub Med and Google Scholar, were used for conducting a comprehensive search to collect information and data. Results: In this review, a total of 10 spices have been compiled with a brief description of their origin, part used, chemical constituents, mechanism of action, methods of experiment, model animals, and reported beneficial effects in diabetes with other pharmacological activities. Conclusion: The observed results of this study indicate the possibility of developing a therapeutic strategy called alternative and complementary medicine for the management of diabetes. The results also provide a starting point for researchers working with bioactive dietary plants with anti-diabetic potential.
Keywords: Diabetes mellitus